Different Types of Beef and Pord Using Histogram Texture and K-Means Clustering Method - Heribertus Himawan; Widya Wiratama (Journal of Applied Intelligent System, 2018)
The largest source of protein needed by the human body comes from meat. Basically a high number of buyers and beef is much more expensive than other meats giving chances to irresponsible parties to mix beef with pork, In the Islamic religious teachings, pork is forbidden because consuming pork there is a physical, psychological and very easy to be contaminated by bacteria. Humans have the limitation of identifying beef and pork manually using the senses of human vision are still many weaknesses and less effective. In this research, meat image extraction applies histogram and clustering by applying K-Mean. By applying this method is expected to help to group the image of meat with a high degree of accuracy.